DISTRIBUTION VARIANTS OF SOMATOTYPE IN HEALTHY AND PATIENTS WITH ACNE BOYS AND GIRLS FROM PODILSKY REGION OF UKRAINE - Gunas, І.V.; Maievskyi, О.Ye.; Dmitrеnkо, S.V.; Mаkаrchuk, І.М.; Terekhovska, О.І.; Cherepakha, O.L.; Ocheretna, O.L. (World of Medicine and Biology, 2017)
Set peculiarities of distribution variants somatotype in healthy and patients with acne boys and girls from Podilsky region of Ukraine. In patients with acne compared with healthy young boys found significantly higher percentage of people mesomorphic and meso-endomorphic somatotype and a smaller percentage of people ecto-mesomorphic somatotype. In patients with acne girls compared with healthy girls found significantly higher percentage of people mesomorphic and a smaller percentage of people endomorphic somatotype. The rest of the percentages by somatotype (ectomorphic and medium intermediate in both sexes, and ecto-mesomorphic and meso-endomorphic in girls) between patients and normal subjects were not significantly differ. As in boys and in girls were not found significant differences or trends in the distribution variants somatotype between groups of patients with acne of various degrees of severity.
Keywords: somatotypes distribution; acne; boys; girls